Verdicts (Fatawa) of Contemporary Islamic Scholars on Suicide Bombing: a Jurisprudential Analysis - AbdulHameed Badmas Yusuf; AbdulWaheed Olarewaju Yakub (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2025)
Suicide bombing, a tactic employed in the contemporary time during war period, has generated intense debates among contemporary Muslim scholars across the globe as regards its  permissibility in Islamic law. Because of the utmost important nature of issues involved, diverse legal verdicts (fatawa) have been issued by some of these Muslim scholars; some of them oppose the act, while some others accept it as a means of resistance, with both groups premising their positions on specific textual evidences as well as legal principles.  Hence, this study aims at critically examining and analyzing legal verdicts (fatawa) of prominent contemporary Muslim scholars on the permissibility and otherwise of suicide bombing, exploring the jurisprudential underpinnings of their opinions. Utilizing a qualitative research, these verdicts shall be discussed to understand different perspectives of selected scholars on the issue. Also, primary sources employed for this research are Islamic jurisprudence texts, scholarly articles and fatawa collections. Findings reveal divergent opinions among scholars due to the variety in the interpretation of relevant texts of the Qur’an and Sunnah. Muslim scholars with the moderate perspective, generally condemn suicide bombing, citing Quranic prohibitions on taking innocent lives. But those with the radical perspective accept it, justifying it as a means of resistance. This study highlights the complexities of Islamic jurisprudence on suicide bombing. While divergent opinions exist on the issue, the most preponderant opinion is the outright rejection of suicide bombing in Islamic law. This research emphasizes the need for proper understanding of the texts and context in addressing very sensitive issues like suicide bombing which is associated with extremism.